The Nutrigenetics and Nutrigenomics of the Dietary Requirement for Choline - CORBIN, KAREN D. (Prog Mol Biol Transl Sci, 2012)
Advances in nutrigenetics and nutrigenomics have been instrumental in demonstrating that nutrient requirements vary among individuals. This is exemplified by studies of the nutrient choline, in which gender, single-nucleotide polymorphisms, estrogen status, and gut microbiome composition have been shown to influence its optimal intake level. Choline is an essential nutrient with a wide range of biological functions, and current studies are aimed at refining our understanding of its requirements and, importantly, on defining the molecular mechanisms that mediate its effects in instances of suboptimal dietary intake. This chapter introduces the reader to challenges in developing individual nutrition recommendations, the biological function of choline, current and future research paradigms to fully understand the consequences of inadequate choline nutrition, and some forward thinking about the potential for individualized nutrition recommendations to become a tangible application for improved health.